A novel ratiometric electrochemical assay for ochratoxin A coupling Au nanoparticles decorated MoS2 nanosheets with aptamer. (20th September 2018) - Wang, Yonghong; Ning, Ge; Bi, Hao; Wu, Yaohui; Liu, Gaoqiang; Zhao, Yunlin
Abstract: A novel aptamer sensor for ratiometric ochratoxin A (OTA) detection was constructed based on the host-guest competition mode. Firstly, the aptamer modified with methylene blue (MB) at its terminal was fixed on the surface of the gold electrode via the host-guest recognition with β-cyclodextrin (β-CD). Then the MoS2 nanosheets/Au NPs nanocomposites were used for the signal amplification. When OTA was present, the configuration of MB-aptamer transformed from vertical linear to G-quadruplex, thus making itself unable to get close to the electrode surface and causing a decrease in the redox current of the MB-aptamer. Whereas the free ferrocenecarboxylic acid could recognize and occupy the vacant site and produce signals in the current, resulting in the "ratiometric" effect. Consequently, on the basis of the "dual-signal" principle, a highly sensitive detection of OTA was made, indicating that the OTA concentration had a linear response to the signal of sensor between 0.1 nM and 50 nM, and as low as 0.06 nM OTA had been detected. Overall, this method for OTA detection was constructed easily with high sensitivity and specificity, providing a significant platform for highly efficient detection of OTA in biological samples. Graphical abstract: Image 1 Highlights: A novel electrochemical sensor for ochratoxin A detection was developed. MoS2 nanosheets-Au NPs nanocomposites were used for the signal amplification. OTA aptamer ensures the specificity of detection. The merit of β-CD with superior recognition capability was employed. The ratiometric strategy could avoid the majority of the interferences and maintain higher precision.